An assessment of the impact of legal regulation on financial security in OECD countries - Robertas Vaitkus; Asta Vasiliauskaite (Journal of Risk and Financial Management, 2022)
The recurrent economic and financial crises expose the state, enterprises, and households to a range of financial risks and negative financial consequences. As a result, governments are seeking the most efficient measures of legal regulation and other measures ensuring financial security in order to address financial insecurity. The financial security can be considered from a variety of perspectives, and this research proposes that microeconomic and macroeconomic indicators be taken into account when assessing the financial security situation. The results of this research confirmed that legal regulation has a significant positive impact on financial security in OECD countries during the analysis period. Based on the results of the study, it can be argued that legal regulation, including anti-corruption measures, must be an essential part of the financial security strategies being developed. The studies carried out provide a platform for further research, which will allow identification of regulatory measures that would most effectively contribute to financial security needs in individual OECD countries.
Keywords: E60; F50; F52; 330; financial security; legal regulation; sustainable economy; economic policy; risk management